2020
DOI: 10.1523/eneuro.0326-19.2020
|View full text |Cite
|
Sign up to set email alerts
|

Response-Related Signals Increase Confidence But Not Metacognitive Performance

Abstract: Confidence judgements are a central tool in metacognition research. In a typical task, participants first perform perceptual (first-order) decisions and then rate their confidence in these decisions. The relationship between confidence and first-order accuracy is taken as a measure of metacognitive performance. Confidence is often assumed to stem from decision-monitoring processes alone, but processes that co-occur with the first-order decision may also play a role in confidence formation. In fact, some recent… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 57 publications
5
9
0
Order By: Relevance
“…Previous studies have shown that certain physical image properties, such as stimulus contrast or the variability in stimulus elements, can impact confidence judgments (Boldt et al, 2017;de Gardelle & Mamassian, 2015;Herce Castanon et al, 2019;Spence et al, 2016;Zylberberg et al, 2014). Others have suggested that observers use non-normative strategies to estimate confidence (e.g., Filevich, Koß, & Faivre, 2020;Maniscalco, Peters, & Lau, 2016;Peters et al, 2017;Winter & Peters, 2021;Zylberberg et al, 2014), much like we do here. Our work differs from previous studies in that we provide both a Bayesian model and an alternative that explains deviations from optimality.…”
Section: Discussionsupporting
confidence: 61%
“…Previous studies have shown that certain physical image properties, such as stimulus contrast or the variability in stimulus elements, can impact confidence judgments (Boldt et al, 2017;de Gardelle & Mamassian, 2015;Herce Castanon et al, 2019;Spence et al, 2016;Zylberberg et al, 2014). Others have suggested that observers use non-normative strategies to estimate confidence (e.g., Filevich, Koß, & Faivre, 2020;Maniscalco, Peters, & Lau, 2016;Peters et al, 2017;Winter & Peters, 2021;Zylberberg et al, 2014), much like we do here. Our work differs from previous studies in that we provide both a Bayesian model and an alternative that explains deviations from optimality.…”
Section: Discussionsupporting
confidence: 61%
“…The weaker link between trajectories and confidence in patients with schizophrenia may be related to slower and noisier motor behaviour, or to the tendency of people with schizophrenia to neglect relevant internal cues to control motor actions. 54 The fact that metacognitive performance was preserved in patients with schizophrenia despite a decreased link between confidence and trajectories suggests that senso rimotor signals may globally up or downregulate confidence estimates, with no influence on the calibration between confi dence and firstorder performance as reported recently. 54…”
Section: Relationships Between Action Execution and Metacognitive Permentioning
confidence: 81%
“…54 The fact that metacognitive performance was preserved in patients with schizophrenia despite a decreased link between confidence and trajectories suggests that senso rimotor signals may globally up or downregulate confidence estimates, with no influence on the calibration between confi dence and firstorder performance as reported recently. 54…”
Section: Relationships Between Action Execution and Metacognitive Permentioning
confidence: 81%
“…Our results provide confirmatory evidence that the findings reported by Siedlecka et al (2019) were a result of motor activity. Additionally, Filevich et al (2020) conclude that key presses in continuous report conditions served as an additional source of evidence available for both the metacognitive judgment and biased participants toward more liberal confidence responses. A similar conclusion comes from the research on perception of voluntary action where both active and passive movements produced overconfidence (Charles et al, 2020).…”
Section: Motor Information Influences Visual Awareness Judgmentsmentioning
confidence: 87%
“…Although it cannot be ruled out that in this task the additional response itself or the visual information from the additional task cue were responsible for the observed effect, two other recent studies show an effect of action on confidence ratings. Faivre et al (2020) have shown that sensorimotor conflicts might decrease metacognitive efficiency (a quantitative measure of participants' level of metacognitive ability, given a certain level of 2AFC task performance), and Filevich et al (2020) have presented that continuous report paired to stimulus presentation leads to higher confidence ratings; however, there was no evidence that absolute confidence judgments or metacognitive efficiency varies with the presence or absence of overt responses.…”
Section: Introductionmentioning
confidence: 99%